KAWASAN RETRET KATOLIK DI KEUSKUPAN AGUNG PONTIANAK - Bilia, Tesalonika Dimitri Santa; Kalsum, Emilya; Caesariadi, Tri Wibowo (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2025)
A retreat is an activity that involves withdrawing from daily routines to a quiet and safe place, where one can deepen one's spirituality and gain a better understanding of oneself, others, and God. In the Catholic tradition, retreats play an important role in nurturing faith through prayer, reflection, and discussion. However, the retreat facilities in the Archdiocese of Pontianak are not commensurate with the growing number of Catholics. Out of a total of approximately 738,000 Catholics, only 14 retreat houses are available. As a result, most retreat activities are conducted in places not specifically designed for such purposes, thereby diminishing the quality of the spiritual experience. The objective of this design project is to create a retreat area with facilities that can support and accommodate the spiritual activities of Catholics in the Archdiocese of Pontianak. The design method follows R. Whitaker's eight-step process, including problem identification, needs analysis, concept synthesis, and design evaluation. The approach used is a functional approach, involving analysis of space, users, activities, and inter-space relationships. The design resulted in eight building masses, with the chapel as the central structure, surrounded by participant accommodation facilities, a convent house, staff quarters, a dining hall, an educational area, and an open communal space. Vegetation was incorporated into the design as both a natural buffer and an element that enhances the cooling and aesthetic appeal of the area.